Imaging to optimize gynecological radiation oncology. Issue 3 (7th March 2022) - Kidd, Elizabeth A
Abstract : Gynecological cancers have particularly benefited from the increasing use of imaging to guide radiation treatment planning for both external beam radiation and brachytherapy. While the different gynecological cancers have varying use of imaging, certain trends predominate. CT represents an economical choice for evaluating initial disease extent or potential metastasis at follow-up, particularly for endometrial and ovarian cancers. F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/CT is particularly useful for assessing the initial disease extent and longer term treatment response of squamous predominant cancers, including cervical, vaginal, and vulvar cancers. With its excellent pelvic soft tissue discrimination, MRI provides the greatest assistance in evaluating the local extent of gynecological tumors, including initial evaluation for non-operative endometrial and vulvar cancer, and assessment before, after and during brachytherapy for cervix, locally recurrent endometrial, and primary vaginal cancers. With more limited availability of MRI, ultrasound can also help guide brachytherapy, particularly during procedures. The benefits of using imaging to better spare bone marrow or earlier assessment of treatment response are topics still being explored, in particular for cervical cancer. As imaging along with radiation oncology technologies continue to evolve and develop, such as with MRI-linacs and ultra high dose rate (FLASH) radiation, we may continue to see increasing use of imaging for advancing gynecological radiation oncology.